The Impact Of Social Partnership On The Environment - Ep Chedli, Mariem Kchaich (Journal of Economic Development, Environment and People, 2016)
The multidimensional social problems that everyone seeks to remedy them are very complex and no actor can confront them on their own. So the different parties have to work together by creating relations of partnerships. The State has long been the main actor in the control and regulation of social relations. However, in recent years there has been a rapid decline in their role given the enormous charge and lack of resources. Hence the need for the intervention of other parties. Some review of literature explores the conceptualization of social partnership in order to meet the needs of the organization or solve organizational problems. More and more large companies and multinationals get started on a voluntary approach to social responsibility and have begun to move closer to certain social enterprises by concluding partnership agreements. The purpose of this study was to study the social transformation that follows the creation of a relation of a social partnership between a social enterprise and a company that has involved a strategy of social responsibility. Then, we will present the environment to finally study the impact of social partnership on the environment; on economic, cultural and political dimensions.